Symmetrical azine colorimetric and fluorometric turn-off chemosensor for formaldehyde detection - Nurul Hidayah,; Purwono, Bambang; Pranowo, Harno Dwi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Azine derivative 6,6’-((1E,1’E)-hydrazine-1,2-diylidenebis(methanyly-lidene))bis(3,4-dimethoxy-aniline) CHA has been synthesized by condensation of 6-nitroveratraldehyde with malononitrile followed by reduction using 10% Pd/C and hydrazine hydrate. In the presence of formaldehyde, CHA chemosensor in ethanol showed a yellow-to-red color change observable by the naked eyes and ‘turn off’ type fluorescence quenching in ethanol. This phenomenon was confirmed by UV-Vis, fluorescence and 1H NMR spectroscopy. The CHA spectra in ethanol was shifted from 412 to 509 nm after addition of formaldehyde. Fluorescence intensity of CHA gradually decreased with the increase of formaldehyde concentrations. Furthermore, paper strips loaded-CHA were fabricated and served to detect formaldehyde qualitatively. The detection limit of the CHA probe to formaldehyde is 0.2 M.